First report of naturalization of Houttuynia cordata Thunb. 1783 (Piperales: Saururaceae) in South America - Válka Alves, Ruy José (2013)
A relatively large and established population of Houttuynia cordata from Itatiaia National Park in Brazil represents the first record of naturalized Saururaceae in South America. Although the species is potentially invasive, unknown mechanisms have prevented its spread to other localities between 1940, when it was recorded in cultivation in Brazil, and the present. The nearest known naturalized population is situated 5,600 km away, in Costa Rica, Central America.